2005
DOI: 10.1002/glia.20148
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic increases in intracellular Ca2+, and the release of MCP‐1, RANTES, and IL‐6 by astrocytes treated with opiates and HIV‐1 Tat

Abstract: Recent evidence suggests that injection drug users who abuse heroin are at increased risk for CNS complications from human immunodeficiency virus (HIV) infection. Opiate drugs may intrinsically alter the pathogenesis of HIV by directly modulating immune function and by directly modifying the CNS response to HIV. Despite this, the mechanisms by which opiates increase the neuropathogenesis of HIV are uncertain. Herein we describe the effect of morphine and the HIV-1 protein toxin Tat 1-72 on astroglial function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
259
4
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 210 publications
(282 citation statements)
references
References 95 publications
18
259
4
1
Order By: Relevance
“…Another explanation is that MLK3 has also been recently reported to modulate p38 MAPK activity (in addition to JNK) , suggesting that p38 MAPK may have also been involved in gp120-induced hippocampal neuron losses. Lastly, although our striatal cultures are highly enriched in neurons (Singh et al, 2004), with negligible microglia (~0.14%) or astroglia (~1%), we cannot exclude the possibility that contaminating glia might mediate some aspects of Tat or gp120 neurotoxicity (Vesce et al, 1997;El-Hage et al, 2005). Studies in progress are specifically addressing this issue.…”
Section: Discussionmentioning
confidence: 97%
“…Another explanation is that MLK3 has also been recently reported to modulate p38 MAPK activity (in addition to JNK) , suggesting that p38 MAPK may have also been involved in gp120-induced hippocampal neuron losses. Lastly, although our striatal cultures are highly enriched in neurons (Singh et al, 2004), with negligible microglia (~0.14%) or astroglia (~1%), we cannot exclude the possibility that contaminating glia might mediate some aspects of Tat or gp120 neurotoxicity (Vesce et al, 1997;El-Hage et al, 2005). Studies in progress are specifically addressing this issue.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that acute morphine stimulation can induce calcium signaling El-Hage et al, 2005) and ERK phosphorylation (Belcheva et al, 2003), while prolonged exposure affected proliferation (Stiene-Martin et al, 2001) and proteomic profile (Suder et al, 2009) in primary astrocytes. The absence of direct transcriptional effects of morphine in astrocytes in the current study may be explained by the low level of l opioid receptors in our cultures, which is consistent with previous reports (Ruzicka et al, 1995;Stiene-Martin et al, 1998).…”
Section: Discussion the Gc-dependent Component Of Morphineinduced Sigmentioning
confidence: 99%
“…In the present study, some chemokiens, such as MCP-5 and sTNFR1, were identified in ACM and METH-ACM. MCP-5 is a mouse homologue to MPC-1 (El-Hage et al, 2005). In addition, treatment with MRP induces the secretion of MCP-1 from astrocytes (El-Hage et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…MCP-5 is a mouse homologue to MPC-1 (El-Hage et al, 2005). In addition, treatment with MRP induces the secretion of MCP-1 from astrocytes (El-Hage et al, 2005). On the other hand, the biological functions of the sTNFR1 are not completely understood.…”
Section: Discussionmentioning
confidence: 99%